Galactan induces macrophage M0 to M1 conversion to combat colon cancer - Meng, Yue; Yang, Guang; Ren, Ai; Qu, Yunhe; Wang, Xue; Mayo, Kevin H.; Zhou, Yifa; Song, Chengcheng (Food Science and Technology Research, 2024)
A 3-O-methylated-galactan WCCP-N-b from Cantharellus cibarius polarizes RAW264.7 macrophages, bone marrow-derived macrophages (BMDMs), and peritoneal macrophages (PEMs) leading to enhanced secretion of cytokine TNF-α and subsequent cytotoxic effects on HCT116 and CT26 colon cancer cells. Investigation into the mechanism of action suggests that WCCP-N-b polarizes macrophages by targeting Toll-like receptor 2 and activation of MAPKs and NF-κB signaling pathways. Overall, our results indicate that this linear 3-O-methylated-galactan inhibits colon cancer cells via conversion of M0 to M1 macrophages.